A ciência em circulação nas esferas públicas: o jornalismo científico em universidades de Minas Gerais e suas repercussões - Silva, Ana Eliza Ferreira Alvim da (2019)
This research projected a retrospective view about the discursive production of scientific journalism practiced in three universities from Minas Gerais (UFMG, UFLA and UFV), considering online textual news available in their websites, published in a period of 15 years (2004-2018), and referring to research related to water issues. The study was also extended to repercussive journalistic texts published by press and other broadcasters. The objective was to understand the performance of such texts in stimulating dialogue and debate about scientific research in public spheres. So, we used Habermas theoretical framework, considering the Theory of Communicative Action as a parameter for the analysis of the science popularization (SP) and the public communication of science (PCS). Thus, we are guided by a dialogical perspective, capable of contributing to the construction of a practical knowledge enlightened in public opinion and to subsidize political decisions in democratic contexts. To contemplate this last point, we also analyze the argumentation of bills that were processed in ALMG about the water theme, in order to observe possible relations with the argumentative discourse of scientific journalism. The news articles included in the sample were analyzed by Critical Discourse Analysis (CDA), with emphasis on the analysis of textual aspects related to comprehensibility and journalistic organization and analysis of the text structure as an argument. The speeches from legislature were analyzed through the perspective of the argumentative structure. The main findings include: 1) Preliminary surveys show that the publication of scientific journalism texts by universities occurred in relatively low flow compared to the total number of news publications in their websites (less than 3% are articles about research), and these results are better when there are better investment conditions in organizational communication. 2) Through scientific journalism, we are far from the practices of SP and PCS related to the perspective of dialogue with community, as proposed by TCA. The texts are presented under a diffusionist perspective, highlighting that: 2.1) there are some weaknesses regarding the accessibility of language to a non-specialized public; 2.2) they are based on values that represent a limited perspective of sustainability, and stated as assumptions, which limits dialogue and debate on points that may not be a consensus among population; 2.3) they bring discursive absences that limit the stimulus to dialogue - we highlight that of actors and voices from community; 2.4) although they are constituted around questionable validity claims, they bring few critical questions to the arguments, including readers’ comments; 3) There is little interface between the guidelines of scientific journalism and the texts discussed at ALMG. 4) So far, the practice undertaken to share science with society through journalism has mobilized still fragile flows in the ‘world of life’, and between it and the System, when talking about water. We considered that an effective public policy for SP/PCS (or at least institutional policies) would represent the institutionalization of necessary devices to bring these initiatives closer to communicative action, in order to update the components of the ‘world of life’ to an emancipatory perspective.